Ligature Materials and postmortem Findings in Hanging Cases Brought for Autopsy at. a Tertiary Care Hospital of Sindh. Pakistan - Salman Ahmed Farsi Kazi, Waheed Ali Nayhoon, Shahid Kamran, Amna Mangi,shrat Bib!, Jamshed-ell-Qadir Memon, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To study the ligature materials and postmortem findings in hanging cases brought for autopsy at a tertiary care hospital of Sindh. Pakistan Methods: The current retrospective study was conducted in the department of Forensic Medicine and Toxicology LUMHS Jamhoro, Hyderabad and Medico-legal section of Liaquat University Hospital Hyderabad. study covers the duration ofAugust 2014 to July 2017. A sample of 100 autopsy cases was selected according to criteria of inclusion and exclusion. Ligature material used and postmortem examination findings were noted in a preformed Profroma. Data variables were noted, compiled, tabulated and analyzed on Excel sheet. Study variables were analyzed by descriptive statistics. Results: Of 100 autopsy cases, male were 83% and 17% were female. Majority of cases belonged to fourth decade (38°..). Ligature mark was categorized as above, at the level and below the level of thyroid cartilage were noted in 94"o. 2°,4) and 4% of cases respectively (P=0.001). Nylon rope (42%), jute rope (169.0 and cotton rope (11%) were most common in male while cotton Dopatta (7%) was common among female. Tongue protrusion (81%). bluish discoloration (79%), petechiae (71%) and salivary stains (37%) were common noted postmortem findings. Conclusion: The present study reports nylon rope as most common ligature in male and cotton dopatta in female. Tongue protrusion. bluish discoloration, petechiae and salivary stains were promient postmortem findings.